Are the “100 of the world’s worst” invasive species also the costliest? - Cuthbert, Ross N.; Diagne, Christophe; Haubrock, Phillip J.; Turbelin, Anna J.; Courchamp, Franck (Biological invasions, 2022)
Biological invasions are increasing worldwide, damaging ecosystems and socioeconomic sectors. Two decades ago, the “100 of the world’s worst” invasive alien species list was established by the IUCN to improve communications , identifying particularly damaging ‘flagship’ invaders globally (hereafter, worst ). Whilst this list has bolstered invader awareness, whether worst species are especially economically damaging and how they compare to other invaders (hereafter, other ) remain unknown. Here, we quantify invasion costs using the most comprehensive global database compiling them (InvaCost). We compare these costs between worst and other species against sectorial, taxonomic and regional descriptors, and examine temporal cost trends. Only 60 of the 100 worst species had invasion costs considered as highly reliable and actually observed estimates (median: US$ 43 million). On average, these costs were significantly higher than the 463 other invasive species recorded in InvaCost (median: US$ 0.53 million), although some other species had higher costs than most worst species. Damages to the environment from the worst species dominated, whereas other species largely impacted agriculture. Disproportionately highest worst species costs were incurred in North America, whilst costs were more evenly distributed for other species; animal invasions were always costliest. Proportional management expenditures were low for the other species, and surprisingly, over twice as low for the worst species. Temporally, costs increased more for the worst than other taxa; however, management spending has remained very low for both groups. Nonetheless, since 40 species had no robust and/or reported costs, the “true” cost of “some of the world’s worst ” 100 invasive species still remains unknown.